Au-ZnO: a tunable localized surface plasmonic nanocomposite - Mishra, Y. K.; Mohapatra, S.; Singhal, R.; Avasthi, D. K.; Agarwal, Dinesh C.; Ogale, S. B. (Applied Physics Letters, 2008)
In this letter, we report the thermal processing controlled tunability of localized surface plasmon resonance (LSPR) of Au nanoparticles embedded in ZnO matrix. Au-ZnO nanocomposite films were prepared by atom beam cosputtering and were annealed from 200 to 600 degrees C in Ar. A regular redshift similar to 110 nm (from 505 to 615 nm) in LSPR peak with increase in annealing temperature up to 600 degrees C is observed. Transmission electron microscopy results confirm the formation of Au nanoparticles supported by ZnO nanorods at annealing temperature of 600 degrees C. The Au-ZnO nanocomposite exhibits significant enhancement in the Raman signal for C(70) molecules. (C) 2008 American Institute of Physics.

VLS-like growth and characterizations of dense ZnO nanorods grown by e-beam process - Agarwal, Dinesh C.; Chauhan, R. S.; Avasthi, D. K.; Sulania, I.; Kabiraj, D.; Thakur, P.; Chae, K. H.; Chawla, Amit; Chandra, Ramesh; Ogale, S. B.; Pellegrini, G.; Mazzoldi, P. (Journal of Physics D-Applied Physics, 2009)
We present a new approach to produce ZnO nanorods in a reproducible manner at a temperature lower than other physical vapour deposition techniques, such as the vapour-liquid-solid mechanism. Arrays of well-aligned ZnO nanorods of uniform diameter have been synthesized on the Si substrate precoated with Au, using a simple electron beam evaporation method without the flow of any carrier gas. Scanning electron microscopy and atomic force microscopy characterizations show that as-grown nanorods are well aligned and uniform in diameter. X-ray diffraction measurements and clear lattice fringes in high-resolution transmission electron microscopy image show the growth of good quality polycrystalline hexagonal ZnO nanorods and a < 0 0 2 > growth direction. The polarization-dependent studies of near edge x-ray absorption fine structure (NEXAFS) are performed to investigate the electronic structure of the zinc and oxygen ions. The analysis of NEXAFS spectra at different angles of incidence of photon flux indicates the formation of ZnO nanorods having anisotropic behaviour of O and Zn states. The photoluminescence spectrum exhibits strong ultraviolet emission at 385 nm and the UV-visible spectrum also shows a band-gap transition around 390 nm indicating the good quality of nanorods. The catalytic growth mechanism of the ZnO nanorods is discussed on the basis of experimental results in this work.